2022
DOI: 10.1523/jneurosci.1045-22.2022
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Theta and Episodic Memory

Abstract: Computational models of rodent physiology implicate hippocampal theta as a key modulator of learning and memory (Buzsáki and Moser, 2013; Lisman and Jensen, 2013), yet human hippocampal recordings have shown divergent theta correlates of memory formation. Herweg et al. (2020) suggest that decreases in memory-related broadband power mask narrowband theta increases. Their survey also notes that the theta oscillations appear most prominently in contrasts that isolate memory retrieval processes and when aggregatin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 53 publications
5
21
0
Order By: Relevance
“…The resonance frequency of h CA1 pyramidal neurons (2.9 Hz) we uncovered in single neuron recordings closely matches the in vivo theta rhythm of human hippocampus (i.e. 1-4 Hz, 17,19,57 . The temporal domain at which human hippocampus operates is thus slower compared to rodents as theta-rhythm in mice and rats occur at higher frequencies (i.e.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The resonance frequency of h CA1 pyramidal neurons (2.9 Hz) we uncovered in single neuron recordings closely matches the in vivo theta rhythm of human hippocampus (i.e. 1-4 Hz, 17,19,57 . The temporal domain at which human hippocampus operates is thus slower compared to rodents as theta-rhythm in mice and rats occur at higher frequencies (i.e.…”
Section: Discussionsupporting
confidence: 72%
“…Interestingly, the theta rhythm is the only oscillatory brain rhythm that inversely scales with brain size across mammals, in contrast to alpha, beta and gamma rhythms, which are similar across mammalian brains 16,17 . In human hippocampus, theta rhythm is 1 -4 Hz [16][17][18][19] compared to 4 -10 Hz in rats 2,20 .…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…We conducted a more naturalistic, self-constraint autobiographical memory task. Rudlor and colleagues ( 83 ) recently showed that this theta power reduction may be associated with broadband activity. The specific experimental design of the present study may allow for a more comprehensive and dynamic test of this notion.…”
Section: Discussionmentioning
confidence: 96%
“…Subsequent studies have replicated the alpha decreases and gamma increases in large subject samples (Burke et al, 2014), but the theta increases have been somewhat elusive (Herweg, Solomon, & Kahana, 2020) except for studies that either specifically focused on the lowest frequencies within the theta band (Lin et al, 2017) or studies that separated narrowband and broadband components (Rudoler, Herweg, & Kahana, 2022). Studies of episodic recollection have observed similar spectral patterns of retrieval success.…”
Section: Introductionmentioning
confidence: 99%